The transoceanic 1755 Lisbon tsunami in Martinique - Roger, J. (2020)
On 1 November 1755, a major earthquake of estimated M (w)=8.5/9.0 destroyed Lisbon (Portugal) and was felt in the whole of western Europe. It generated a huge transoceanic tsunami that ravaged the coasts of Morocco, Portugal and Spain. Local extreme run-up heights were reported in some places such as Cape St Vincent (Portugal). Great waves were reported in the Madeira Islands, the Azores and as far as the Antilles (Caribbean Islands). An accurate search for historical data allowed us to find new (unpublished) information concerning the tsunami arrival and its consequences in several islands of the Lesser Antilles Arc. In some places, especially Martinique and the Guadeloupe islands, 3 m wave heights, inundation of low lands, and destruction of buildings and boats were reported (in some specific locations probably more enclined to wave amplification). In this study, we present the results of tsunami modeling for the 1755 event on the French island of Martinique, located in the Lesser Antilles Arc. High resolution bathymetric grids were prepared, including topographic data for the first tens of meters from the coastline, in order to model inundations on several sites of Martinique Island. In order to reproduce as well as possible the wave coastal propagation and amplification, the final grid was prepared taking into account the main coastal features and harbour structures. Model results are checked against historical data in terms of wave arrival, polarity, amplitude and period and they correlate well for Martinique. This study is a contribution to the evaluation of the tele-tsunami impact in the Caribbean Islands due to a source located offshore of Iberia and shows that an 8.5 magnitude earthquake located in the northeastern Atlantic is able to generate a tsunami that could impact the Caribbean Islands. This fact must be taken into account in hazard and risk studies for this area.